Improving the learning process in anatomy practical sessions of chiropractic program using e-learning tool - Nilesh Kumar Mitra; Htar Htar Aung; Mangala Kumari; Joachim Perera; Anupa Sivakumar; Anudeep Singh; Vishna Devi Nadarajah (Elsevier, 2021)
Background: To accommodate the increased number of students and shorter learning time, anatomy instructors are increasingly developing web-based learning resources that can fulfil program-specific anatomical learning objectives and replace existing learning environment of the anatomy laboratory sessions. The study evaluated the quantitative change in the performance score in gross anatomy by replacement of face-to-face demonstration with an e-learning tool in practical sessions of chiropractic program. Materials & methods: This quasi-experimental one-group pre-test and post-test design was employed longitudinally in two consecutive cohorts of semester 2 students. Teacher-led demonstration was used for first two sessions. E-learning tool was used in the next two sessions. Structured OSPE-based pre-test and post-test were held before and after the sessions. Wilcoxon Signed-Rank test was used to find out percentage of students showing improvement in the post-test score. Pearson correlation coefficient between pre-test and post-test scores was also done. A short questionnaire assessed the use of e-learning tools by the students. Results: The mean difference between the post-test and pre-test score was higher in e-learning tool-led practical sessions. In 2018 cohort, 85.4% and 83.3% of students and 2019 cohort, 95% of students secured higher scores in post-test in two sessions with e-learning tool. In 2018 cohort, 62% and 70% of students and 2019 cohort, 81% and 70% of students secured higher scores in post-test in two sessions with teacher-led demonstration. A lower R2 coefficient was observed between post-test and pre-test scores in sessions with e-learning tool. Perception analysis indicated that majority of students agreed about e-learning tool allowing them to revise identification of anatomical structures themselves. Conclusion: The e-learning tool was able to raise the post-test score in a higher percentage of students, indicating improved learning process in practical sessions using e-learning tools. The study would motivate anatomy instructors to use web-based learning tools to identify structures during the laboratory sessions.